Loss of FBP1 by aPKC-ι/Snail Pathway-Mediated Repression Promotes Invasion and Aerobic Glycolysis of Intrahepatic Cholangiocarcinoma - Gao, Meng; Mei, Chengjie; Guo, Yonghua; Xia, Peng; Zhang, Hao; Liu, Yinyi; Yao, Ye; Jiang, Xiang; Yuan, Yufeng; Qian, Yawei (Frontiers in Oncology, 2021)
Intrahepatic cholangiocarcinoma (ICC) is one of the most commonly diagnosed malignancies worldwide, and the second most common primary liver tumor. The lack of effective diagnostic and treatment methods results in poor patient prognosis and high mortality rate. Atypical protein kinase C-ι (aPKC-ι) is highly expressed in primary and metastatic ICC tissues, and regulates epithelial mesenchymal transition (EMT) through the aPKC-ι/P-Sp1/Snail signaling pathway. Recent studies have correlated aberrant glucose metabolism with EMT. Given the vital role of FBP1 in regulating glucose metabolism in cancer cells, we hypothesized that aPKC-ι downregulates FBP1 in ICC cells through the Snai1 pathway, and enhances glycolysis and metastasis. We confirmed the ability of aPKC-ι promotes glycolysis, invasion and metastasis of cancer cells, and further demonstrated that FBP1 inhibits the malignant properties of ICC cells by antagonizing aPKC-ι. Our findings provide novel insights into the molecular mechanisms of ICC progression and metastasis, as well as a theoretical basis for exploring new treatment strategies.